Anna Langfus, la Shoah, le silence et la voix - Decout, Maxime 1979-; Wolf, Nelly 1953-; Jakubczuk, Renata; Kucharuk, Sylwia (Brill, 2024)
"Anna Langfus participated in a major renewal of Holocaust literature which had been mainly testimonial and witness-focused prior to her publications. She is the author of theater plays and of three novels: Le Sel et le soufre (1960), Les Bagages de sable (1962), awarded with the Prix Goncourt, and Saute, Barbara (1965). She experienced the horrors of the Holocaust, but she refused to express her grief through autobiography. Through her work she explores, without pathos, the tragedy of those who survived, and what Anna Langfus herself calls "la maladie de la guerre": the war disease. This books examines, among other issues, the specificity of Langfus's texts. Written at a time when an ethos of victimization, repentance, and sometimes Manichaeism was dominant, Langfus's they urge us to keep any form of idealization or false consolation at a distance"--
Keywords: Langfus, Anna -- 1920-1966; Judenvernichtung -- Motiv; Zweiter Weltkrieg; Theater; Literatur; Langfus, Anna / 1920-1966 / Criticism and interpretation; Holocaust, Jewish (1939-1945), in literature; Holocauste, 1939-1945, dans la littérature; Langfus, Anna / 1920-1966; Holocaust, Jewish (1939-1945) in literature; Criticism, interpretation, etc; Essays; Literary criticism; Critiques littéraires; Aufsatzsammlung